Sepsis: Primary indication for peripartum hysterectomies in a South African setting - Catherine Cluver; Lize Jansen van Vuuren (South African Medical Association, 2016)
Background. Peripartum hysterectomies are lifesaving procedures but definitions vary. Indications are variable and dependant on resources and geographical factors.Objectives. To evaluate the incidence, aetiology and complications associated with peripartum hysterectomies in a tertiary hospital in South Africa.Methods. A retrospective audit at an academic referral centre over a 5-year period from February 2009 to March 2014 was performed. Procedures from a gestation of 24 weeks until 6 weeks postpartum were included.Results. One hundred and sixty cases met inclusion criteria. Nine case records were unavailable. The incidence was 2.77 per 1 000 deliveries. Main indications were sepsis (60, 39.7%), atony (24, 15.9%), morbidly adherent placenta (21, 13.9%), tears (14, 9.3%), uterine rupture (8, 5.3%), placenta praevia (7, 4.6%) and unclassified bleeding (6, 4.0%). There were 6 maternal deaths. Five related to sepsis and one to hypovolaemic shock. One hundred and thirty-eight (91.4%) women required high or intensive care admission.Conclusion. Sepsis is an important aetiology for peripartum hysterectomies, particularly in southern Africa. The high rate of sepsis may be due to HIV infection, low socioeconomic standards, late diagnosis, limited access to healthcare, sterility issues and differences in the definition and inclusion criteria used for a peripartum hysterectomy.